Ecosystem-based management for marine fisheries an evolving perspective - Belgrano, Andrea; Fowler, Charles W. 1941- (Cambridge University Press, 2011)
Showing how big-picture patterns can help overcome the failures of conventional management, this book is ideal for students, researchers and professionals involved with marine fisheries. It explores not only the current practice of the 'ecosystem approach' to fisheries management but also its critical importance to even larger perspectives. The first section gives a valuable overview of how more and more of the complexity of real-world systems is being recognized and involved in the management of fisheries around the world. The second section then demonstrates how important aspects of real-world systems, involving population dynamics, evolution and behavior, remain to be taken into account completely. This section also shows how we must change the way we think about our involvement in, and the complexity of, marine ecosystems. The final chapters consider how, with the use of carefully chosen macroecological patterns, we can take important steps towards more holistic management of marine fisheries